2017
DOI: 10.1080/09585192.2016.1270985
|View full text |Cite|
|
Sign up to set email alerts
|

HRM in dynamic environments: Exploitative, exploratory, and ambidextrous HR architectures

Abstract: The current economic crisis has brought to the fore the need for firms to deal with ambiguity and complexity. Hence, firms need a specific balance between exploration and exploitation in order to keep pace with varying and changing environmental conditions. Hitherto, there is limited research that has examined the nexus of HR architectures, ambidexterity, and environmental dynamics. In this conceptual paper we ask: How do HR architectures serve as a means of balancing exploitative and exploratory learning in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(63 citation statements)
references
References 85 publications
1
62
0
Order By: Relevance
“…This study has shown how microfoundations may be acquired, developed, diffused and embedded throughout an organisation. This contributes to strategic HR theory as we propose a bespoke HR architecture for BMI, as we demonstrate that BMI is largely about developing people, in a purposeful manner (Hansen et al, 2017). However, the emergence of the gig economy in the New Normal in recent years, which generally reflects the substantive role of more temporary and seasonal employment and a more transient workforce, challenges the hegemony of a development system-centric BMI HR architecture.…”
Section: Contributionsmentioning
confidence: 72%
“…This study has shown how microfoundations may be acquired, developed, diffused and embedded throughout an organisation. This contributes to strategic HR theory as we propose a bespoke HR architecture for BMI, as we demonstrate that BMI is largely about developing people, in a purposeful manner (Hansen et al, 2017). However, the emergence of the gig economy in the New Normal in recent years, which generally reflects the substantive role of more temporary and seasonal employment and a more transient workforce, challenges the hegemony of a development system-centric BMI HR architecture.…”
Section: Contributionsmentioning
confidence: 72%
“…This suggests that researchers are more Beatty et al, 2003Bayo-Moriones et al, 2013Gelens et al, 2013Nieves & Quintana, 2018Lepak & Snell, 2002 Gonz alez & Verano-Tacorante, 2004De Vos & Dries, 2013McDonnell et al, 2016Schmidt, Pohler, et al, 2018Purcell et al, 2004Kulkarni & Ramamoorthy, 2005Kang et al, 2007Bryant & Allen, 2009Zhou et al, 2012 2. Individual Quadrant of the HR Architecture 2.1 Q1: for HC with High Uniqueness and High Value 9 1 0 1 2 L opez-Cabrales et al, Nijs et al, 2014Chuang et al, 2016Lepak et al, 2007Boon & Kalshoven, 2014Tlaiss et al, 2017Nesheim et al, 2007 Way et al, 2015Hansen et al, 2019…”
Section: Resultsmentioning
confidence: 99%
“…Following this, they proposed corresponding employment modes organizations should adopt. Similarly, Hansen et al (2019) considered the role of environmental dynamics and proposed specific HR architectures that enabled organizational exploration, exploitation, and ambidexterity in high velocity, moderately dynamic and heterogeneous environments, respectively.…”
Section: Extension and Critiquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Both benefi ted entrepreneurial innovation and entrepreneurial competitiveness. Hansen et al (2019) mentioned that organizational vision and strategy were the most important part in the promotion of organizational performance in an industry. Innovation education stressed the most on the establishment of vision and strategies to cultivate innovation ability in order to acquire the entrepreneurial competitiveness in the industry by constant R&D of innovation products.…”
Section: H2: Technology Innovation Shows Remarkably Positive Relationmentioning
confidence: 99%